(untitled) (Research, Society and Development, 2025)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by difficulties in communication, social interaction, and behavior. The objective of this study was to analyze the patient´s caregivers’ perception about the healthcare services in Cruzeiro do Sul, Acre, considering the quality, effectiveness, accessibility, and continuity offered. Given the increase in case numbers and challenges faced by families, this research evaluated the perception of 111 ASD children’s caregivers regarding healthcare services in Cruzeiro do Sul–AC. This is an observational type research with a quantitative approach and cross-sectional design, using a structured questionnaire. It was observed a predominance of males (68.5%), with an age between 3 and 8 years (55.9%), and diagnosis by the age of 3 in 87.4% of cases. ADHD was the main comorbidity. Regarding access to healthcare services, 92.8% consider them accessible, and 99.1% rated the physical environment as adequate. All children are supported by a multidisciplinary team and 93.7% approve the provided medical care. However, 58.6% reported stress due to time spent in waiting and 15.4% experienced some disrespect. It is concluded that the municipality has a functional support network, but still requires advances in professional qualification, reduced waiting times and an enhanced more efficient primary care.